Novel 3-(6-methylpyridin-2-yl)coumarin-based chalcones as selective inhibitors of cancer-related carbonic anhydrases IX and XII endowed with anti-proliferative activity - Haytham O. Tawfik; Moataz A. Shaldam; Alessio Nocentini; Rofaida Salem; Hadia Almahli; Sara T. Al-Rashood; Claudiu T. Supuran; Wagdy M. Eldehna (Journal of Enzyme Inhibition and Medicinal Chemistry)
Carbonic anhydrases (CAs) are one of the promising targets for the development of anticancer agents. CA isoforms are implicated in various physiological processes and are expressed in both normal and cancerous cells. Thus, non-isoform selective inhibitors are associated with several side effects. Consequently, designing selective inhibitors towards cancer-related hCA IX/XII rather than the ubiquitous cytosolic isozymes hCA I and II is the main research objective in the field. Herein, a new series of 3-(6-methylpyridin-2-yl)coumarin derivatives 3 and 5a–o was designed and synthesised. The CA inhibition activities for the synthesised coumarins were analysed on isoforms hCA I, II, IX, and XII. Interestingly, both cancer-linked isoforms hCA IX/XII were inhibited by the prepared coumarins with inhibition constants ranging from sub- to low-micromolar range, whereas hCA I and II isoforms haven’t been inhibited up to 100 µM. Furthermore, the target coumarins were assessed for their antitumor activity on NCI-59 human cancer types.